P58 Efficacy of budesonide/formoterol in COPD patients with a post-bronchodilator fev1 50 to <70% of predicted normal: pooled analysis across four phase iii/iv studies. (15th November 2016) - Jorup, C; James, GD; Pemberton, K; Eckerwall, G
Abstract : Background: GOLD guidelines have changed from classifying COPD severity using pre-bronchodilator FEV1 to classifying severity based on post-bronchodilator FEV1. We therefore conducted a pooled post-hoc analysis of four budesonide/formoterol (Symbicort ® ) Turbuhaler ® trials in COPD (which included patients based on pre-bronchodilator FEV1 ), assessing efficacy and safety of budesonide/formoterol in the post-bronchodilator FEV1 50– <70% of predicted normal (PN) subpopulation versus the all-patient population. This analysis supported the EU label change for Symbicort ® Turbuhaler ® to: 'symptomatic treatment of patients with COPD with FEV1 < 70% PN (post-bronchodilator) and an exacerbation history despite regular bronchodilator therapy'. Methods: Four randomised, double-blind, active- and/or placebo-controlled, studies in patients with moderate to very severe COPD were analysed. Key study inclusion criteria were pre-bronchodilator FEV1 ≤50% PN; use of short-acting bronchodilator; ≥1 exacerbation in the past 12 months. Primary endpoints for the analysis were 3-month pre- and 3- and 12-months post-bronchodilator FEV1 and exacerbation rates at 3- and 12-months. Secondary endpoints included dyspnoea score, total symptom score, reliever medication use, night-time awakening and St George's Respiratory Questionnaire. Results for the post-bronchodilator FEV1 50 – <70% PN subpopulation were compared with the all-patient population. Results: Of 3787 randomised patients, 832 (22.0%) had post-bronchodilator FEV1 50 – <70% PN. Baseline characteristics of the FEV1 50 – <70% subpopulation and the all-patient population were similar, except for baseline FEV1 parameters. The benefit of budesonide/formoterol versus placebo and formoterol on the primary and secondary endpoints were generally consistent between the FEV1 50 – <70% subpopulation and the all-patient population across all four studies and in the pooled analysis (Figure 1 ). No new safety signals were identified. Conclusions: In patients with COPD, the clinical efficacy and safety of budesonide/formoterol compared with placebo and formoterol was consistent between the post-bronchodilator FEV1 50 – <70% PN subpopulation and the all-patient population, confirming the positive benefit/risk ratio in COPD patients with a post-bronchodilator FEV1 <70% PN and a history of exacerbations.